2017
DOI: 10.1002/cbic.201700498
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive DNAzyme‐Based Ca2+ Detection Boosted by Ethanol and a Solvent‐Compatible Scaffold for Aptazyme Design

Abstract: Functional DNA includes aptamers and DNAzymes, and metal ions are often importantf or achieving the chemical functions of such DNA. Biosensors based on functional DNA have mainly been tested in aqueous buffers. By introducing organic solvents with much lower dielectric constants, the interaction between metal ions and DNA can be significantly enhanced, and this might affect the performance of DNA-based biosensors. In this work, the effect of ethanol on the activity of the EtNa DNAzyme was studied for Ca 2 + de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…We chose a DNAzyme that required a very high metal concentration for catalysis so that we could better observe the effect of freezing. The EtNa DNAzyme is highly specific for Na + among the monovalent metals, but it has almost no activity in water when the Na + concentration is below 100 m m ; cleavage occurs efficiently with 1 m Na + . Its activity can be significantly enhanced by adding an organic solvent, such as ethanol, attributed to stronger electrostatic interactions between Na + and DNA in solutions with a lower dielectric constant .…”
Section: Etna Dnazyme Cleaves Faster With Na+ After Freezingmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose a DNAzyme that required a very high metal concentration for catalysis so that we could better observe the effect of freezing. The EtNa DNAzyme is highly specific for Na + among the monovalent metals, but it has almost no activity in water when the Na + concentration is below 100 m m ; cleavage occurs efficiently with 1 m Na + . Its activity can be significantly enhanced by adding an organic solvent, such as ethanol, attributed to stronger electrostatic interactions between Na + and DNA in solutions with a lower dielectric constant .…”
Section: Etna Dnazyme Cleaves Faster With Na+ After Freezingmentioning
confidence: 99%
“…Its activity can be significantly enhanced by adding an organic solvent, such as ethanol, attributed to stronger electrostatic interactions between Na + and DNA in solutions with a lower dielectric constant . EtNa also works with a divalent metal, Ca 2+ , allowing for a systematic comparison of the effects of metal ions . Therefore, we selected EtNa for this study.…”
Section: Etna Dnazyme Cleaves Faster With Na+ After Freezingmentioning
confidence: 99%
“…Interestingly, EtNa activity drastically decreases at ethanol concentrations beyond 72 % (v/v) ethanol, where the B‐form helix of DNA is converted into the A‐form that (in contrast to ribozymes) seems to be incompatible with the formation of the active DNAzyme conformation. Given that EtNa shows cooperative binding of and activation by Ca 2+ (in contrast to Mg 2+ ) it can also be used as an ultrasensitive biosensor capable of detecting Ca 2+ levels down to 1.4 μ m Ca 2+ . Eutectic freezing can also activate EtNa, while other DNAzymes that depend on divalent or trivalent metals are inhibited under these conditions .…”
Section: Activity Enhancement By Freezing Evaporation and Presence Omentioning
confidence: 99%
“…Given that EtNa shows cooperative binding of anda ctivation by Ca 2 + (in contrastt oM g 2 + ) [202] it can also be used as an ultrasensitive biosensor capable of de-tectingC a 2 + levels down to 1.4 mm Ca 2 + . [203] Eutectic freezing can also activate EtNa, while other DNAzymes that depend on divalent or trivalent metals are inhibited under these conditions. [204] This again highlights the interchangeability of freezing, organic dehydration or evaporation to achieve activation of metal-independent nucleic acid catalysts.…”
Section: Freezingand Dehydration Induced Deoxyribozyme Catalysismentioning
confidence: 99%
“…Although the detailed structure and enzymatic mechanism of the 17E DNAzyme have not been elucidated, biophysical studies have shown the importance of Mg 2+ binding and non-canonical hydrogen bonding in the catalytic core for catalysis [53][54][55]. It is noted that an RNA-cleaving DNAzyme exhibiting high activity in the presence of high ethanol concentration have been reported [27,28]. The active complex of this enzyme might be stable enough to overcome the destabilization effect of ethanol, unlike the case of 17E(S).…”
Section: Effects On the 17e Dnazymementioning
confidence: 99%